Effects of Plyometric Training to Improve a Physical Capacity and Athletic Performance to High School Students 17-18 Years Old - Benzidane, Houcine; Bensikaddour, Habib; Mokrani, Djamel (My University, 2015)
The research aims to know the effect of implying plyometric method to improve the upgrading capacity and the digital achievement in the effectiveness of the long jump. Where researchers used the experimental method to the nature of research, and the sample consisted of high school students of Relizane province (Algeria). The 56 students were selected and divided into two groups in equal number, while the tests used were the broad jump test of the stability, vertical jump, and digital test achievement in the long jump. After statistical processing of the raw results, the researchers concluded that the use plyometric method in physical education and sports classes for high school students has improved the upgrading capacity, as well as digital achievement in the long jump, in addition to the superiority of the experimental sample over the control sample in the test results. The research finding confirms the effectiveness of using plyometric exercises with students while teaching in improving the digital achievement with the experimental research sample.
Keywords: Plyometric Method, Upgrading Ability, Digital Achievement, Long Jump